Examination of Leisure Attitudes' Effect on Self-Confidence Levels of University Students - Hakan Akdeniz; Özlem Keskin; Kemal Erdoğan (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2021)
The aim of this study is to examine the relationship between university students' leisure time attitudes and self-confidence levels. 1095 (487 female, 608 male) students who studied at Kocaeli University participated in the study voluntarily. As a data collection tool in research, "Personal Information Form" created by researchers, "Leisure Attitude Scale" developed by Ragheb and Beard (1982) the validity and reliability of which was adapted to Turkish by Gürbüz and Akgül (2011), and the "Self-Confidence Scale" developed by Akın (2007) were used. In the analysis of the data, frequency analysis was used to examine the participants' personal information distributions, skewness-kurtosis values were examined to determine whether the data showed normal distribution, Manova, Tukey and Post-Hoc tests were used to determine the differences between the variables, correlation analysis was used to establish relations. As a result of the analysis; It was found that there was a high positive correlation between leisure time attitude and self-confidence scales of students from the Faculty of Communication, Faculty of Engineering, Faculty of Education and Faculty of Sport Sciences (p<0.05). Behavioural subdimension levels of male students were significantly higher than female students (p<0.05). Emotional, cognitive and self-confidence subscales of the leisure attitude scale were not significantly different according to gender (p>0.05). Significant differences were found between faculty variables with leisure attitude scale, sub-dimension and self-confidence scales (p<0.05). It can be said that Sport Sciences, Education, Engineering and Communication Faculty students with high leisure attitudes have high self-confidence levels.